2019
DOI: 10.1088/1755-1315/305/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effect of Clerodendrum sp and Acanthus illicifolius Methanol Extraction on Blood Profile of Male Mice Induced by Benzo(α)pyrene

Abstract: Benzo(α)pyrene is one of carcinogenic PAH substances which commonly produced by many different sources of polutant. The study was conducted in order to determine the effect of methanol extraction of Clerodendrum sp and Acanthus illicifolius which known to be two of common mangrove plants on the blood profile of male mice induced by benzo(α)pyrene (one of polycyclic aromatic hydrocarbon/PAH). Thirty male mice (Mus musculus) of ddy strain from Lampung Vetenary Agency were used to conduct the study. Completely ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…The leucocyte count is higher in the day time than the night hours, while stress produce increase in lymphocyte concentration and decrease in neutrophil concentration [22]. Poisonous chemical like benzo(α)pyrene and dichlorvus elicit increase in leucocyte concentration [24,25]. In rats, the lymphocyte and neutrophil represent 60-75% and 12-38% of leucocyte count respectively, while eosinophil, basophil and monocyte levels vary within 0-7% of leucocyte count [22,26].…”
Section: Resultsmentioning
confidence: 99%
“…The leucocyte count is higher in the day time than the night hours, while stress produce increase in lymphocyte concentration and decrease in neutrophil concentration [22]. Poisonous chemical like benzo(α)pyrene and dichlorvus elicit increase in leucocyte concentration [24,25]. In rats, the lymphocyte and neutrophil represent 60-75% and 12-38% of leucocyte count respectively, while eosinophil, basophil and monocyte levels vary within 0-7% of leucocyte count [22,26].…”
Section: Resultsmentioning
confidence: 99%
“…These microbes possibly believed to have beneficial uses such as probiotic, antibiotic, and bioactive products and else (Subagiyo, Muhammad, & Wilis, 2017). The recent study also indicated that some mangrove shrubs, such as Acanthus ilicifolius contain antioxidant (Widiastuti, Arifianti, Khairani, Christianto, Ara, & Maharani, 2019). Other studies showed that Bacillus sp.…”
Section: A Margasari Mangrovementioning
confidence: 99%
“…Antioksidan merupakan senyawa yang dapat menangkal efek berbahaya dari radikal bebas. Dalam proses menangkal radikal bebas antioksidan dapat memperlambat atau mencegah proses oksidasi dimana proses oksidasi ini dapat menyebabkan beberapa penyakit dan kerusakan seperti kerusakan protein dan DNA (Widiastuti et al, 2019). Tubuh memiliki antioksidan endogen yang berasal dari dalam tubuh dan dalam menetralkan radikal bebas dapat dibantu oleh antioksidan eksogen (Khaira, 2010).…”
Section: Hasil Dan Pembahasanunclassified